Construction of an NAND logic gate based on molecularly imprinted dual-emission quantum dot composites for the detection of antibiotics. Issue 15 (18th March 2019) - Ma, Yimei; Jin, Xiaoyong; Xing, Yonglei; Ni, Gang; Peng, Juan
Abstract : Molecularly imprinted dual-emission quantum dot composites (DEQDs@MIPs) were prepared and used to construct NAND molecular logic gates for the simultaneous detection of SS and KS. Abstract : In this study, an NAND molecular logic gate based on molecularly imprinted functionalized quantum dot (QDs@MIPs) composites was constructed for the simultaneous detection of streptomycin sulphate (SS) and kanamycin sulfate (KS). To achieve this goal, two kinds of CdTe QDs with green (QDG ) and red emission (QDR ) colours were prepared. Then, QDG @MIPs were used for the detection of SS in the concentration range of 3.00–118 μM, and the limit of detection (LOD) was 0.22 μM. QDR @MIPs were used for the estimation of KS in the concentration range of 3.00–105 μM, and the limit of detection (LOD) was 0.24 μM. The molecularly imprinted dual-emission quantum dot composites (DEQDs@MIPs) exhibited two emission peaks at 525 nm and 625 nm with excitation at 360 nm. DEQDs@MIPs were used as fluorescent probes for the rapid and simultaneous detection of SS and KS. In this system, the input of SS and KS and the output of the fluorescence value coincided with the NAND logic gate; thus, the NAND molecular logic gate can be constructed using DEQDs@MIPs for the simultaneous detection of SS and KS.